Evaluación de la efectividad del riego, mediante la utilización de tres tipos de aspersores en zona con alta incidencia de viento, en parcelas con mezcla forrajera de pastos en cantón Cayambe, provincia Pichincha - Aceldo Toromoreno, Byron Andrés (2011)
The present investigation, was carried out in the Ecuadorian Sierra North, in the Association San Vicente of Porotog, belonging to the County of Pichincha, in the canton Cayambe, Parish Cangahua, at distance 79 Km of the city of I Remove and 19 Km of Cayambe, with coordinated geographical 78° 07´35´´ of western longitude and 0° 03´19´´ of south latitude and an altitude of 3360 msnm. The characteristic agroclimáticas is: temperature annual average was of 10.30 ºC, precipitation annual average of 560.80 mm, humidity relative 84.92%, speed of the wind 6.22 km/h. The floor is of texture sandy franc, since they contain 56% of sand, 28% files and 16 clay%; pH of 5.90 (lightly sour) As siembra material it was used grass seeds among mixture of gramineous and leguminous. Different aspersores types were evaluated (Senninger 3/4", Tropper 3/4" and Rosi 3/4") in three treatments and three repetitions. The utilized design was Blocks Totally at random DBCA, the comparisons of the stockings were made with the test of Ranges Multiples of Duncan...........